2022
DOI: 10.17515/resm2022.501ma0814
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the effect of ultra fine rice husk ash over slag based geopolymer concrete

Abstract: investigates the production of sustainable geopolymer concrete using industrial wastes such as Ground Granulated Blast Furnace Slag and ultra fine Rice Husk Ash (URA). The effect of partial substitution of GGBS with URA in proportions such as 0, 5, 10, 15 and 20 percent is investigated for workability, drying shrinkage, compressive and tensile strength over different ages of concrete ranging from 7 to 90 days. A micro structural investigation through Scanning Electron Microscope and X-Ray Diffraction Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Workability is seen to be increased up to 25% cement replacement, as noted by R. Srinivasan et al also, strength in compression, split and flexural increases up to 10% replacement [8]. There will significantly enhance workability, compressive strength, and tensile strength by using GGBFS and rice husk ash [9]. Moulshree Dubey et al found the addition of GGBFS and metakaolin in binary concrete enhances the concrete performance [10].…”
Section: Introductionmentioning
confidence: 86%
“…Workability is seen to be increased up to 25% cement replacement, as noted by R. Srinivasan et al also, strength in compression, split and flexural increases up to 10% replacement [8]. There will significantly enhance workability, compressive strength, and tensile strength by using GGBFS and rice husk ash [9]. Moulshree Dubey et al found the addition of GGBFS and metakaolin in binary concrete enhances the concrete performance [10].…”
Section: Introductionmentioning
confidence: 86%
“…In order to mitigate the negative consequences associated with OPCdriven industries, it is imperative to explore alternative construction materials that significantly reduce cement consumption, thereby enhancing the sustainability of the construction sector. Such alternatives could encompass the incorporation of recycled materials or the implementation of more efficient production methodologies that curtail waste generation and energy consumption [5,6]. By conducting a thorough investigation and embracing the adoption of these viable substitutes, a meaningful contribution can be made towards mitigating the ecological consequences of the construction sector and forging a more sustainable trajectory for the future [7,8].…”
Section: Introductionmentioning
confidence: 99%